CON_PCA method to solve the human monochromacy color blindness - Ahmed, Basaeir Y.; Ali, Huda A. (Institute of Advanced Engineering and Science, 2023)
Color blindness is an inherited genetic ocular disorder. Acquired or congenital color blindness can become a major cause of problems in everyday life tasks. Contributing to solving the trouble of color blindness is important. Because the problem of color blindness leads to the non-discrimination of data seen by the infected person. Data visualization can contribute to solving the hassle of color blindness. This paper proposed a new technique using data visualization ideas that may contribute to easy data recognition. Our focus has been on monochromacy color blindness. The results are based on the famous Ishihara data sets measuring color blindness. The efficiency of the results was mathematically proven using equations and images via a website to simulate color blindness.